GROWTH AND MATURITY HYPOTHESES ON DIVIDEND POLICY: INDONESIAN PERSPECTIVE - Ismiyanti, Fitri (Journal of Management and Business, 2011)
This research is aimed at testing the increase and decrease in dividends in relation to market reaction intertwined with the profitability of the firm. The main contribution of this study is the separation of the market reaction based on the firm’s lifecycle. The differentiation of the firm’s lifecycle purports to analysis whether there is distinguished influence between the increase (decrease) in dividends on firms at growth stage and that on firms at maturity stage. Data used are manufacturing firms listed on the Indonesia Stock Exchange for the period of 1994-2008.